2001
DOI: 10.1177/082585970101700103
|View full text |Cite
|
Sign up to set email alerts
|

Demoralization Syndrome — a Relevant Psychiatric Diagnosis for Palliative Care

Abstract: I Hopelessness, loss of meaning, and existential distress are proposed as the core features of the diagnostic category of demoralization syndrome. This syndrome can be differentiated from depression and is recognizable in palliative care settings. It is associated with chronic medical illness, disability, bodily disfigurement, fear of loss of dignity, social isolation, and-where there is a subjective sense of incompetence-feelings of greater dependency on others or the perception of being a burden. Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
363
0
15

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 492 publications
(388 citation statements)
references
References 59 publications
5
363
0
15
Order By: Relevance
“…A considerable amount of literature has illuminated the presence of powerlessness and helplessness in the workplace of nurses [14,23,56,58,59,81] and doctors [52]. Patients' suffering from chronic illness as well as progressive malignant disease [7,9,24,32,40,71] and the next of kin's experiences have also been described in terms of powerlessness and helplessness. Such experiences have been illuminated in different groups of next of kin, for example parents having a disabled child [20], parents of stillborn children [41,49,64], informal caregivers of patients with chronic diseases [11] and cancer patients [18,46], and also within home care [11,79].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable amount of literature has illuminated the presence of powerlessness and helplessness in the workplace of nurses [14,23,56,58,59,81] and doctors [52]. Patients' suffering from chronic illness as well as progressive malignant disease [7,9,24,32,40,71] and the next of kin's experiences have also been described in terms of powerlessness and helplessness. Such experiences have been illuminated in different groups of next of kin, for example parents having a disabled child [20], parents of stillborn children [41,49,64], informal caregivers of patients with chronic diseases [11] and cancer patients [18,46], and also within home care [11,79].…”
Section: Introductionmentioning
confidence: 99%
“…Demoralisation syndrome has been described as a persistent inability to cope, together with associated feelings of helplessness, hopelessness, meaninglessness, subjective incompetence and diminished self-esteem [8]. According to Clarke and Kissane, the syndrome is of clinical relevance in palliative care and, in addition, "it is arguably the main reason people seek psychiatric treatment, yet is a concept largely ignored in psychiatry" [8,40]. The concepts of powerlessness and helplessness may also provide prospective predictions concerning health, as indicated by the increased sense of powerlessness that accompanied deterioration in health among older men and mature women [69], and later adjustment disorders among family caregivers that had perceived helplessness when taking care of a dying person [75].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive care to alleviate the existential distress of terminally ill cancer patients is one of the main focuses of recent medical literature [1,12]. Empirical studies have suggested that terminally ill cancer patients have a variety of existential concerns, associated with serious psychological morbidity such as desire for death and suicide [3,5,8,9,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…A death with dignity is considered good, and a death without dignity is feared [13]. The importance of dignity in dying is expressed both by patients and caregivers as well as in philosophical and political contexts [17,20,22,24,26].…”
Section: Introductionmentioning
confidence: 99%